Tradisi Salat Al-Hifzi Bagi Penghafal Al-Qur’an di Ponpes Raudhah Tahfizh Al-Qur’an “Baitul Azhar” Amuntai, KALSEL - Najib Irsyadi (UIN Sunan Kalijaga Yogyakarta, 2014)
This paper tries to explain the phenomena of Hadith as traditions of Muslim society. The study of the phenomenon of Hadith is also called as ”Living Hadith” defined as the religious phenomenon such as modes of conduct or responses to interpretation of Hadith texts. These traditions can be classified into three categories: oral, written, and practical one. The object of this research is the practice of Shalat al-Hifdzi located at Ponpes Tahfizh Al-Qur’an “Baitul Azhar’’ Amuntai. Using the phenomenological approach and observation-interview type of method, the research shows that the significance of both practice of Shalat al-Hifdzi particularly for Huffadz and its exercise (Riyadhah) is to come nearer (Taqarrub) to God and to have easier process memorizing the Qur’an.[Tulisan ini mencoba untuk menjelaskan fenomena hadis yang telah menjadi sebuah tradisi masyarakat Muslim. Kajian terhadap gejala-gejala fenomena berdasarkan hadis juga disebut sebagai